In Silico Analysis Highlights the Diversity and Novelty of Circular Bacteriocins in Sequenced Microbial Genomes - Bingyue Xin; Hualin Liu; Jinshui Zheng; Chuanshuai Xie; Ying Gao; Dadong Dai; Donghai Peng; Lifang Ruan; Huanchun Chen; Ming Sun (mSystems, 2020)
ABSTRACT Consumer demand for “fresh food” with no chemical preservatives has prompted researchers to pay more attention to natural antimicrobial peptides such as bacteriocins. Nisin is currently the most widely used food biopreservative among the bacteriocins; however, its applications are restricted due to its low stability at neutral and alkaline pH values. Circular bacteriocins have potent antimicrobial activity against foodborne pathogens, show exceptional stability, and have great potential to be developed as biopreservatives. Here, we take advantage of the precursor peptides of 15 reported circular bacteriocins to devise an in silico approach to identify potential circular bacteriocins in sequenced microbial genomes. A total of nearly 7,000 putative precursor peptides were identified from 86 species of bacteria and further classified into 28 groups based on their amino acid similarity. Among the groups, 19 showed low similarity (less than 50%) to any known precursor peptide of circular bacteriocins. One novel circular bacteriocin in group 11, cerecyclin, showed the highest identity (34%) to the known circular bacteriocin enterocin NKR-5-3B and was selected for verification. Cerecyclin showed antimicrobial activity against several Gram-positive bacteria, inhibited the outgrowth of Bacillus cereus spores, and did not exhibit hemolysis activity. Moreover, it showed 4-fold- to 8-fold-higher antimicrobial activity against B. cereus and Listeria monocytogenes than nisin A. Cerecyclin also had increased stability compared to nisin A under neutral or alkaline conditions. This work not only identified a promising food biopreservative but also provided a rich source for novel circular bacteriocins. IMPORTANCE Circular bacteriocins are promising biopreservatives, and it is important to identify more novel circular bacteriocins to enhance the current arsenal of antimicrobials. In this study, we used an in silico approach to identify a large number of novel circular bacteriocins and classified these bacteriocins into 28 groups rather than the 2 groups that were described in previous studies. Nineteen groups were novel and had low similarity (less than 50%) to any known precursor peptides of circular bacteriocins; this finding greatly expands the awareness of the novelty and diversity of circular bacteriocins. A novel circular bacteriocin which we named cerecyclin was identified in the B. cereus group; this circular bacteriocin had great antimicrobial activity against some foodborne pathogens and showed extreme stability. This study not only identified a promising food biopreservative but also provided a rich source for the identification of novel circular bacteriocins and the development of new biopreservatives.